2004
DOI: 10.1093/hmg/ddh331
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of sensitivity of advanced non-small cell lung cancers to gefitinib (Iressa, ZD1839)

Abstract: Gefitinib (Iressa, ZD1839), an inhibitor of epidermal growth factor receptor-tyrosine kinase, has shown potent anti-tumor effects and improved symptoms and quality-of-life of a subset of patients with advanced non-small cell lung cancer (NSCLC). However, a large portion of the patients showed no effect to this agent. To establish a method to predict the response of NSCLC patients to gefitinib, we used a genome-wide cDNA microarray to analyze 33 biopsy samples of advanced NSCLC from patients who had been treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
165
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(175 citation statements)
references
References 30 publications
5
165
0
5
Order By: Relevance
“…We have also compared the gene expression changes in mouse models exposed to gefitinib with those that have been found to predict sensitivity to gefitinib in human NSCLC (16). As shown in Table 3, we found that gefitinib treatment changed the expression levels for 15 of these 131 genes in mice tumors (fold change, >1.5), which correspond to the expression profiles predicting sensitivity to gefitinib in human NSCLC.…”
Section: Oligonucleotide Array Analysis Of Lung Tumors and Normal Tismentioning
confidence: 72%
See 1 more Smart Citation
“…We have also compared the gene expression changes in mouse models exposed to gefitinib with those that have been found to predict sensitivity to gefitinib in human NSCLC (16). As shown in Table 3, we found that gefitinib treatment changed the expression levels for 15 of these 131 genes in mice tumors (fold change, >1.5), which correspond to the expression profiles predicting sensitivity to gefitinib in human NSCLC.…”
Section: Oligonucleotide Array Analysis Of Lung Tumors and Normal Tismentioning
confidence: 72%
“…correspond to the expression profiles predicting sensitivity to gefitinib in human NSCLCs (16). Among them, eight were modulated by gefitinib toward to the normal level (fold change, >1.5).…”
Section: Discussionmentioning
confidence: 86%
“…Using cDNA microarray, increased expression of amphiregulin or TGF-a, known to be the ligands for EGFR, is related with poor response to gefitinib (Kakiuchi et al, 2004). Recently, it was reported that heregulin, ligand for HER3, expression correlates with gefitinib insensitivity (Zhou et al, 2006).…”
Section: Other Molecular Parameters Ligandsmentioning
confidence: 99%
“…To identify such molecules, particularly oncoantigens, we had conducted genome-wide expression profile analysis of 120 clinical lung cancer tissue samples, coupled with enrichment of tumor cells by laser microdissection, and then compared the expression profile data with those in 31 normal human tissues (27 adult and 4 fetal organs; refs. [6][7][8][9][10]. To verify the clinicopathologic significance of the respective gene products, we have established a screening system by a combination of the tumortissue microarray analysis of clinical lung cancer materials and RNA interference technique .…”
Section: Introductionmentioning
confidence: 99%